Controlling Stunting and Community Nutritional Status through Integration of PUSKESMAS and AI: A Case Study in Cilongok, Banyumas - Al-Hakim, Rosyid; Ardianto, Rian; Suryani, Riska; Jayusman, Hadi; Nisa, Khoirun; Nugroho, Ady (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2025)
Stunting remains a critical public health issue in Indonesia, with long-term consequences for children’s cognitive and physical development. This community engagement project aimed to strengthen early detection and prevention of stunting in Rancamaya Village, Cilongok, Banyumas, through the integration of grassroots health education and artificial intelligence (AI) technology. The program involved midwives, Posyandu cadres, and youth from Karang Taruna in a series of educational sessions focused on nutrition, family planning, and child development. Participants were trained to use an AI-based mobile application designed to assist in identifying stunting risk using anthropometric data. The intervention resulted in improved community health literacy, greater responsiveness to early signs of malnutrition, and successful adoption of AI tools by local health workers. This initiative not only demonstrated the feasibility of deploying digital health technologies in rural settings but also underscored the importance of community-driven collaboration in addressing complex health challenges. The program presents a scalable model for similar contexts across Indonesia and beyond.